Pengabdian Mahasiswa Pendidikan Sosiologi dalam Meningkatkan Pemahaman IPS (Ilmu Pengetahuan Sosial) Siswa SMP Negeri 4 Takalar Melalui Metode Pembelajaran Problem Based Learning (PBL) - Anan Dita Asrawati; Risqa Ayu Ramadani; Nawir, Muhammad (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to strengthen the role of students' contributions in improving their understanding of Social Studies (IPS) subjects at SMP Negeri 4 Takalar using the Problem-Based Learning (PBL) method. The method used in this study is Classroom Action Research (CAR) with a qualitative approach that combines observation, interviews, and initial and final exams to assess the effectiveness of teaching. The results of the study indicate that the implementation of the PBL method is successful in improving students' activeness and critical thinking skills in understanding the IPS material, despite challenges such as adaptation to the service and limitations in learning media. The evaluation of this service program emphasizes the importance of good cooperation between universities and schools as well as continuous support for students so that the service provided can provide an optimal impact on improving the quality of education and developing students' interpersonal skills. These findings contribute to the development of active learning strategies that facilitate improving the quality of education at the junior high school level.